Resurrection of the African gecko genus Ancylodactylus Müller, 1907 (Squamata: Gekkonidae) and description of six new species from Kenya - Malonza, Patrick K.; Bauer, Aaron M. (Zootaxa, 2022)
The genus Cnemaspis as presently construed is polyphyletic, with African, South Asian and Southeast Asian clades each representing independent lineages. The name Ancylodactylus Müller, 1907 is available for the African clade of forest geckos and features previously identified as putatively diagnostic of this group (loss or reduction of the second phalanx of digit IV of manus and pes, as well as a markedly dilated basal portions of the digits) are here regarded as characters supporting the monophyly of Ancylodactylus. Six new species of Ancylodactylus are described: A. kenyaensis sp. nov., A. kituiensis sp. nov., A. mathewsensis sp. nov., A. laikipiensis sp. nov., A. spawlsi sp. nov., and A. chyuluensis sp. nov. on the basis of unique combinations of body size, trunk and tail tubercles, median subcaudal scales, precloacal pores, enlarged subdigital plates, ventral color, and throat color and patterning. Ancylodactylus kenyaensis is among the largest members of the genus, reaching 65 mm SVL, whereas A. spawlsi and A. chyuluensis, with maximum SVLs of 30 mm or less, are the smallest of all members of the genus. All these geckos are chiefly scansorial, occurring on tree trunks, fallen logs and/or in rock outcrops. Ancylodactylus kituiensis and A. mathewsensis occur in isolated dryland hilltop forests surrounded by large tracts of arid lands and are locally abundant in suitable rock outcrops or caves, where they occur in small colonies. Ancylodactylus kenyaensis is a montane forest species found on tree trunks with cracks and crevices, whereas A. spawlsi is a montane forest species found in crevices and beneath loose bark of tree trunks as well as in rock crevices and slabs. Ancylodactylus laikipiensis is likewise both rupicolous and arboreal and A. chyuluensis has been taken only from a pitfall trap in a dry forest patch. All the new species are endemic to relatively small, circumscribed areas within Kenya and all occur within protected areas. At present we consider their IUCN conservation status to be Data Deficient. Herpetological surveys are recommended in other unexplored or under-explored forest areas, particularly hilltop montane forests in isolated dryland rocky hills as these may harbor other undescribed Ancylodactylus species or previously undocumented populations of known species.